Atmospheric conditions associated with the exceptional fire season of 2003 in Portugal - Trigo, Ricardo M.; Pereira, José M. C.; Pereira, MáRio G.; Mota, Bernardo; Calado, Teresa J.; Dacamara, Carlos C.; Santo, Fátima E. (International journal of climatology, 2006)
The summer of 2003 was characterised by exceptional warm weather in Europe, particularly during the first two weeks of August, when a devastating sequence of large fires was observed, reaching an amount of circa 450 000 ha, the largest figure ever recorded in Portugal in modern times. They were concentrated in two relatively confined regions of Portugal and a considerable proportion of burnt area was due to fires started on the 2nd and 3rd of August. It is shown that the 850 hPa temperature values observed over Portugal for the 1st and 2nd of August 2003 were the highest recorded since 1958. Using data from synoptic stations covering the entire Portuguese territory, the event was characterised in fine detail, including the evolution of both maximum and minimum temperatures, surface relative humidity, and wind anomaly fields. The different spatial extent of maximum and minimum temperatures is analysed leading to the new all‐time Portuguese records of 47.3 °C for maximum and 30.6 °C for minimum temperatures that were recorded on the 1st of August near the main area of occurrence of the largest fire. Finally, it is shown that the summer of 2003 was preceded by a wet winter followed by a very dry month of May, a precipitation anomalous regime that contributed to a climatic background that favoured the role played by the early August heatwave and the associated meteorological surface conditions. Copyright © 2006 Royal Meteorological Society